What anyone can do : how surrounding yourself with the right people will drive change, opportunity, and personal growth - Bottary, Leo (Routledge, 2018)
Most of us don't seek advice or reach out to others for help very easily. In part, it's because we're conditioned to see life as an individual endeavor rather than a team sport. Or because we believe that asking for help makes us look weak or incapable. We regard self-help as by-yourself-help. News flash: no one in the history of the world has ever achieved any level of happiness or success totally by themselves. In his 1976 book The Long Run Solution, Joe Henderson suggested that becoming truly accomplished at running (or at anything) doesn't typically require us to perform superhuman feats. In fact, success is frequently realized by those who simply do the things anyone can do that most of us never will. In What Anyone Can Do, with the help of Leo Bottary's Year of the Peer podcasts guests (and playful illustrations by Ryan Foland), you'll discover that if you surround yourself with the right people, you'll do the things anyone can do far more often. And when you do that, you and the people around you will realize more of what you want out of business and life. It's that simple. The Power of Peers (2016) made a strong case for how and why formal peer groups are so effective. This book steps outside the formal peer group arena to examine all the important relationships we have in our lives (parents, teachers, spouses, mentors, children, mentees, etc.) and provides a practical approach and specific framework for harnessing their power for your benefit (and theirs) It's what anyone can do. You're anyone, right.